1999
DOI: 10.1080/j.1600-0412.1999.780206.x
|View full text |Cite
|
Sign up to set email alerts
|

Symptom-giving pelvic girdle relaxation in pregnancy, I: Prevalence and risk factors

Abstract: Symptom-giving pelvic girdle relaxation is a considerable problem both in pregnancy and post partum. The occupational risk can possibly be prevented. The syndrome has a great social impact because of the frequent sicklisting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
144
2
5

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(163 citation statements)
references
References 9 publications
12
144
2
5
Order By: Relevance
“…Risk factors for persistent pain were found to be age 30 years or above, a moderate or high ODI in pregnancy, and a history with both PP and LBP during pregnancy. These findings provide important information on women at Although most women recover spontaneously from pregnancy-induced PP during the puerperium, several studies show that a considerable portion have persistent PGP and PP/LBP 3-6 months after delivery, with reported frequencies ranging from 4 to 43 % [9][10][11]24]. The variation may be due to the use of different criteria for both diagnosis and inclusion.…”
Section: Discussionmentioning
confidence: 85%
“…Risk factors for persistent pain were found to be age 30 years or above, a moderate or high ODI in pregnancy, and a history with both PP and LBP during pregnancy. These findings provide important information on women at Although most women recover spontaneously from pregnancy-induced PP during the puerperium, several studies show that a considerable portion have persistent PGP and PP/LBP 3-6 months after delivery, with reported frequencies ranging from 4 to 43 % [9][10][11]24]. The variation may be due to the use of different criteria for both diagnosis and inclusion.…”
Section: Discussionmentioning
confidence: 85%
“…Associations between uncomfortable or physically strenuous work and pelvic pain during pregnancy were found in these studies, but no or only a modest effect was observed for occupational lifting (2,12,13).…”
Section: Discussionmentioning
confidence: 92%
“…The covari- ates that confounded the estimate the most were: parity, overweight, smoking, and not working during day time, while the remaining factors had only a minor influence. In the literature, factors such as working in draft and cold, pushing and pulling, bending and twisting, stress/ depression, and family history of pelvic pain during pregnancy were also identified as risk factors of pelvic pain during pregnancy, but we had no information on these potential confounders and could not include them in the model (2,12,(18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations